Epidemiological Study of the most Important Dermatophyte Infections in Musayyib General Hospital, Iraq (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2024)
Background:Dermatophytes are keratophilic fungi that consider exogenous organisms, and cause serious infections of the skin, hair, and nails. The main goal of the current study is to present a survey of fungal skin infections in Musayyib general hospital of Babylon Province Iraq, through the identification of the incidence of some types of Tineae and the extent of spread in different age groups.Materials and MethodsA256 patients clinically suspected of dermatophytosis, 210 were positive in direct examination and/or culture. From the positive patients' sample that includes skin scrapping, hair fragments, and nailsResultsThe current study showed that Dermatomycosis infected in males more than females with a ratio of 151 (71.90 %) males and 59 (28.09%) females. The highest percentage of infection with Tinea capitis appeared in males , while the lowest percentage of infection with Tinea ungums with a rate equal between males and females. According to age groups.ConclusionsAccording to the findings of the study, it absolves that although Covid 19 pandemic the world went through fundamental changes by increasing the level of understanding and awareness of people to use different sterilizers and detergents. In addition to reducing contact between people and taking care of personal hygiene. Unfortunately, these procedures did not have a positive effect on reducing dermatophytosis infection in Musayyib General Hospital.